Neutrophil CD64 expression levels in IGRA-positive individuals distinguish latent tuberculosis from active disease - Corrêa, Raquel da Silva (2019)
Universidade do Estado do Rio de Janeiro. Faculdade de Ciências Médicas. Laboratório de Imunopatologia. Rio de Janeiro, RJ, Brasil.